Route to Enhancing Remote Epitaxy of Perovskite Complex Oxide Thin Films - Lee, Sangho; Zhang, Xinyuan; Abdollahi, Pooya; Barone, Matthew R.; Dong, Chengye; Yoo, Young Jin; Song, Min Kyu; Lee, Doyoon; Ryu, Jung El; Choi, Jun Hui; Lee, Jae Hyun; Robinson, Joshua A.; et al. (ACS Nano, 2024)
Remote epitaxy is taking center stage in creating freestanding complex oxide thin films with high crystallinity that could serve as an ideal building block for stacking artificial heterostructures with distinctive functionalities. However, there exist technical challenges, particularly in the remote epitaxy of perovskite oxides associated with their harsh growth environments, making the graphene interlayer difficult to survive. Transferred graphene, typically used for creating a remote epitaxy template, poses limitations in ensuring the yield of perovskite films, especially when pulsed laser deposition (PLD) growth is carried out, since graphene degradation can be easily observed. Here, we employ spectroscopic ellipsometry to determine the critical factors that damage the integrity of graphene during PLD by tracking the change in optical properties of graphene in situ. To mitigate the issues observed in the PLD process, we propose an alternative growth strategy based on molecular beam epitaxy to produce single-crystalline perovskite membranes.
Keywords: Building blockes; Complex oxides; Graphenes; High crystallinity; Molecular-beam epitaxy; Oxide thin films; Pulsed-laser deposition; Remote epitaxy; Stackings; Thin-films; complex oxide; graphene; molecular beam epitaxy; pulsed laser deposition; remote epitaxy; spectroscopic ellipsometry; thin film